Pengendalian Kualitas Produksi Jok Mobil Dengan Metode Statistical Quality Control (SQC) - Erniyani, Erniyani; Ahistasari, Asih; Putri, Famelga Clea; Kayatun, Siti Nur; Siswanto, Siswanto (Universitas Muhammadiyah Sorong, 2025)
Increasingly competitive industrial conditions necessitate that companies maintain high product quality to remain competitive. One of the challenges frequently faced by the manufacturing industry is high levels of product productivity, which can impact customer satisfaction and operational efficiency. This study specifically examines the issue of product defects in the car seat production process at PT. ABC. Despite implementing a quality control system, a significant number of product defects were still found. The study used a quantitative approach using Statistical Quality Control (SQC) methods, specifically p-charts, to analyze production and defect data over 16 days. The analysis showed that the proportion of defects varied significantly, with the highest value reaching 55.17% and the lowest at 5.13%. The control chart showed data points approaching the upper control limit, indicating the process was not yet fully stable. Fishbone analysis identified the main causes of defects, including human factors, work methods, raw materials, and machines. Comprehensive improvements to the work system and joint control are needed to increase production process stability and sustainably reduce defect rates.